Terrorism on Asean’s economic growth, does it matter? - Mertha Pessela; Erika Haryulistiani Saksono (Jurnal Inovasi Ekonomi, 2022)
This study provides the impact of terrorism, investment, and government expenditure on economic growth in four ASEAN countries (Indonesia, Philippines, Thailand, and Myanmar). The fix effect model indicates that terrorism and investment have a negative and significant effect on economic growth, while government expenditure has a significant positive impact.